New charts for the assessment of body composition, according to air-displacement plethysmography, at birth and across the first 6 mo of life. Issue 5 (3rd May 2019) - Norris, Tom; Ramel, Sara E; Catalano, Patrick; Caoimh, Carol ni; Roggero, Paola; Murray, Deirdre; Fields, David A; Demerath, Ellen W; Johnson, William
ABSTRACT: Background: Air-displacement plethysmography (ADP) is a good candidate for monitoring body composition in newborns and young infants, but reference centile curves are lacking that allow for assessment at birth and across the first 6 mo of life. Objective: Using pooled data from 4 studies, we aimed to produce new charts for assessment according to gestational age at birth (30 + 1 to 41 + 6 wk) and postnatal age at measurement (1–27 wk). Methods: The sample comprised 222 preterm infants born in the United States who were measured at birth; 1029 term infants born in Ireland who were measured at birth; and 149 term infants born in the United States and 57 term infants born in Italy who were measured at birth, 1 and 2 wk, and 1, 2, 3, 4, 5, and 6 mo of age. Infants whose birth weights were <3rd or >97th centile of the INTERGROWTH-21 st standard were excluded, thereby ensuring that the charts depict body composition of infants whose birth weights did not indicate suboptimal fetal growth. Sex-specific centiles for fat mass (kg), fat-free mass (kg), and percentage body fat were estimated using the lambda-mu-sigma (LMS) method. Results: For each sex and measure (e.g., fat mass), the new charts comprised 2 panels. The first showed centiles according to gestational age, allowing term infants to be assessed at birth and preterm infants to be monitored until they reached term. The second showed centiles according to postnatal age, allowing all infants to be monitored to age 27 wk. The LMS values underlying the charts were presented, enabling researchers and clinicians to convert measurements to centiles and z scores. Conclusions: The new charts provide a single tool for the assessment of body composition, according to ADP, in infants across the first 6 mo of life and will help enhance early-life nutritional management.